How remarkable women lead - Barsh, Joanna (Crown Books, 2011)
Includes bibliographical references and index; Pt. 1. Meaning -- 1. It all begins with meaning -- 2. Your own happiness equation -- 3. Start with your strengths -- 4. A sense of purpose -- 5. Dreamcatcher -- Pt. 2. Framing -- 6. A matter of framing -- 7. The practice of optimism -- 8. Moving on -- 9. Ready for change -- 10. The journey, not the destination -- Pt. 3. Connecting -- 11. A path to belonging -- 12. Your organization as family -- 13. Reciprocity forms relationships -- 14. The tapestry you weave -- 15. On the shoulders of sponsors -- 16. Member of the tribe -- Pt. 4. Engaging -- 17. Crossing the line -- 18. Stand up, speak up -- 19. Make your own luck -- 20. Take the step -- 21. Weathering the heights -- Pt. 5. Energizing -- 22. Energy in your toolkit -- 23. For a quick recovery -- 24. Experience the flow -- 25. Boundless energy; Neal A. Newfield, Ph.D., LICSW (Giver)